Wild Girls in German Literature from Slavonia - Jug, Stephanie (Anafora, 2023)
The paper analyzes the image of the young girl in German literature from Slavonia. The characteristics of young girls are shown on three examples (Victor von Reisner's Das angenehme Erbe, Roda Roda's Die Streiche des Junkers Marius and Wilma Vukelich's Spuren der Vergangenheit), which are then compared to the characteristics of young girls as depicted in German novels for young girls. The elements suggested by Christa Stocker are used in the analysis: explicit and implicit descriptions of movement, naturalness, officiousness, a state of mind attributed to young girls during the period in question and terminology. The analysis and comparison show that only Victor von Reisner portrays the young girl within the norms prescribed by novels for young girls. Roda Roda and Wilma Vukelich give their girl protagonists unusual characteristics that cannot be classified as well-behaved or ill-mannered. Although they show characteristics of wild young girls, i. e. girls that are not stereotypical, they are not judged or sanctioned as ill-mannered. On the contrary, the characteristics that make them seem wild give them a special distinctiveness and character depth which they preserve as adult women as well. The analyses also shows that in all three texts the regional characteristics influence the character of the young girl.